Polycarbonate crowns for primary teeth revisited: Restorative options, technique and case reports - Karthik Venkataraghavan; John Chan; Sandhya Karthik (Wolters Kluwer Medknow Publications, 2014)
Esthetics by definition is the science of beauty - that particular detail of an animate or inanimate object that makes it appealing to the eye. In the modern, civilized, and cosmetically conscious world, well-contoured and well-aligned white teeth set the standard for beauty. Such teeth are not only considered attractive but are also indicative of nutritional health, self esteem, hygienic pride, and economic status. Numerous treatment approaches have been proposed to address the esthetics and retention of restorations in primary teeth. Even though researchers have claimed that certain restorations are better than the others, particularly owing to the issues mentioned above, the search for the ideal esthetic restoration for the primary teeth continues. This paper revisits and attempts to reintroduce the full coverage restoration, namely, polycarbonate crown, for use in primary anterior teeth.